LAJU PENYERAPAN KUNING TELUR TAMBAKAN (Helostoma temminckii C.V) DENGAN SUHU INKUBASI BERBEDA - Adriana Mariska; Muslim .; Mirna Fitrani (Universitas Sriwijaya, 2013)
ABSTRACT The purpose of this study was to determine the effect of different incubation temperatures to the rate of the kissing gouramy (Helostoma temminckiiC.V) yolk absorption, and to know the right time to start feeding in the larval stage. This study was held on January 09th to 13th, 2013 using Completely Randomized Design (CRD) with five treatments namely P1 (26±0.50C), P2 (28±0.50C), P3 (30±0.50C), P4 (32±0.50C) and P5 (34±0.50C).Each treatment was repeated three times. The results showed that the temperature gave significant effect (P>0,05) to rate of yolk absorption, periode of yolk absorption and percentage of larval survival.The highest rate of yolk absorption was P5 (42.24 x 10-5 mm3/hour), but not significantly different fromP4 (41.63 x 10-5 mm3hour-1), and P3 (41.83 x 10-5 mm3hour-1). The fastest periode of yolk absorption was P5 (72 hours) and the longest was P1 (78.67 hours). While the highest larval survival rate was found on P3 (89.87%), on the other hand the lowest survival rate was found on P5 (62.35%). The natural feeding of kissing gouramy fish should be started at 74th hours (3 days, 2 hours) after hatching and larval rearing should use temperature of 300 ± 0.50 C. Keywords: Helostoma temminckii C.V., temperature, yolk absorption